High share of renewables in energy system planning through integration of wind energy - Yeganeh Aliabadi; Younes Noorollahi; Omid Asgari; Mehrab Rezazadeh; Rahim Moltames (Energy Conversion and Management: X)
The present research addresses the current challenges by proposing an approach to identify suitable sites for wind power plants in Qazvin province, Iran, using Geographic Information System (GIS), multi criteria decision-making technique and technical software. In other words, a wind power plant was modeled using HOMER software for technical assessment in two zones at the site identified by GIS software. Twenty-one factors were analyzed to minimize costs and environmental impacts while maximizing power output. The results indicate that Qazvin has significant potential for implementing wind systems, with approximately 1,522 km2 (10 %) of the studied area classified as “highly suitable to suitable”. In contrast, approximately 6,987 km2 (44.19 %) of the studied area are less suitable or not suitable for installation wind systems. Moreover, the technical and physiographic and legal restriction criteria with the weights of 0.54 and 0.08 are the most and least effective in determining the optimal location, respectively. In addition, the sub criteria of wind speed, wind density and distance from power distribution network have the most effectiveness with weights of 0.33, 0.13, and 0.07, respectively. The weight consistency rate is equal to 0.12, which indicates the comparisons are consistent and stable. Besides, the technical results indicate that the annual power capacity of power plant equals aproximatly102 MWh, which the most powers were produced on march with the amount of approximately 6700 and 5000 in zone 1 and zone 2, respectively. The added capacity can effectively fulfill a substantial portion of the province’s demand and influence the province’s energy portfolio.